Issues of Geopoetics in Modern Literary Criticism - O. N. Alexandrova-Osokina (Научный диалог)
The results of the study and systematization of literary research on the problems of geopoetics as a direction in Russian literary criticism are presented in this review article. The relevance of the study is seen in the need to comprehend and systematize the accumulated literary experience in the field of the geopoetic paradigm of literary research. The scope of work identified in the research process is an indicator of a growing scientific interest in the aforementioned problems. In the study of the material, it was shown that the theoretical component of the work is the study of the nature of the geopoetic image, which is understood as the artistic image of the geographical space as a natural, historical-cultural and value-semantic unity. The works representing geopoetic regional models (“texts”) of Russian literature: northern, Crimean, Altai, Ural, Far Eastern, sacred are identified and substantively characterized in the article. The analyzed material allowed us to present a generalized artistic structure of the geopoetic model of the region, including mythopoetic images, natural history and historical-cultural realities, historical aspects of the formation of geopoetic representations, folklore and literary texts. The study represents geopoetic research as a systematic scientific direction uniting scientists from different regions of Russia and having formed within its borders a methodology and scientific tools for identifying and analyzing the geopoetic content of Russian literature. The systematization of the material presented in this article will help create a clear picture of the theoretical and historical-scientific development of the problem.